2008
DOI: 10.1016/j.nlm.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in contextual associative learning

Abstract: The hippocampus plays a critical role in processing contextual information. Although age-related changes in the hippocampus are well documented in humans, nonhuman primates, and rodents, few studies have examined contextual learning deficits in old rats. The present study investigated age-related differences in contextual associative learning in young (6 mo) and old (24 mo) rats using olfactory stimuli. Stimuli consisted of common odors mixed in sand and placed in clear plastic cups. Testing was conducted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Odor discrimination, which involves processing in the OB and higher, is less consistently affected by age (Enwere et al 2004, Prediger et al 2006, Patel and Larson 2009, Kramer and Apfelbach 2004, Luu et al 2008). Odor habituation and dishabituation, which depend on piriform cortex function, were examined in one study of rats, which found intact habituation but impaired dishabituation at 22 months (Guan and Dluzen 1994).…”
Section: Olfactory Behavioral Testing In Senescent Animals and Modelsmentioning
confidence: 99%
“…Odor discrimination, which involves processing in the OB and higher, is less consistently affected by age (Enwere et al 2004, Prediger et al 2006, Patel and Larson 2009, Kramer and Apfelbach 2004, Luu et al 2008). Odor habituation and dishabituation, which depend on piriform cortex function, were examined in one study of rats, which found intact habituation but impaired dishabituation at 22 months (Guan and Dluzen 1994).…”
Section: Olfactory Behavioral Testing In Senescent Animals and Modelsmentioning
confidence: 99%
“…For example, aged nonhuman primates and rodents demonstrate parallel impairments to animals with hippocampal damage on a variety of memory tasks, including tasks measuring spatial memory [1924], temporal order memory [25], contextual memory [26], delayed recognition memory [2729], odor memory [30], and transitive inference [31]. …”
mentioning
confidence: 99%
“…Therefore, age-related changes in the hippocampus may contribute to the present findings in 25 mo old rats. Furthermore, prior studies have reported age-related impairment on other hippocampal dependent spatial tasks in rodent models of aging [1923,25,26]. The encoding of contextual information may be critical to the formation of episodic memories due to the need to form associations among stimuli, actions, and places that compose an event [36].…”
mentioning
confidence: 99%
“…Occasion setting can also be studied under conditions in which contextual cues indicate the circumstances under which a CS is associated with a rewarding US. One very recent and intriguing report finds that aged rats are unable to utilize context cues as occasion setters in an appetitive olfactory task (Luu, Pirogovsky, & Gilbert, 2008). To date, there are only a very small number of papers in the literature that examine renewal in mice.…”
mentioning
confidence: 99%